Analisis Penerapan Pemikiran Ekonomi Al-Ghazali dalam Teori Konsumsi: (Studi Kasus Impulsive Buying dalam Gaya Hidup Muslim di Era Digital) - Zenita Alvina Fauziah; Risma Syan Sabilla; Rifa Khoerunnisa; Lina Marlina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Al-Ghazali's economic thought emphasizes balance in consumption and the importance of avoiding wastefulness and excess. However, in this digital era impulsive buying is increasingly prevalent, including among Muslims. This research is motivated by the behavior of Muslim consumers who tend to be more concerned with satisfaction than needs. The method used is qualitative research with a case study approach, to analyze the application of Al-Ghazali's economic thought in consumption theory. This research method is designed to provide a comprehensive and in-depth understanding of the application of Al-Ghazali's economic thought in the concept of consumption, especially the phenomenon of impulsive buying among Muslims in the digital era. The results show that the phenomenon of impulsive buying is increasingly widespread, triggered by easy access to information and products through digital platforms, as well as the influence of social media. This is often contrary to the principles of consumption taught by Al-Ghazali, who emphasized the importance of simplicity and moderation. This study recommends the need for awareness and education on consumption ethics in Islam to help avoid excessive consumption behavior and prioritize spiritual values in every act of consumption.